A note on the Hertz contact model with nonlinear damping for pounding simulation. - Ye, Kun
Structural pounding during earthquakes has been recently investigated extensively by using different models of impact force. In this paper, reexamination of the Hertz contact model with nonlinear damping is made. Based on this reexamination, the formula used to determine the damping constant in terms of the spring stiffness, the coefficient of restitution and relative approaching velocity of two colliding bodies is found to be incorrect for pounding simulation in structural engineering. In order to correct this problem, a more accurate approximating formula for the damping constant is theoretically derived. The correctness of the derived analytical formula has been confirmed through numerical simulations.
Keywords: Structural pounding; Earthquake; Hertz model; Nonlinear damping; Coefficient of restitution